2019
DOI: 10.3390/separations6020023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gamma Irradiation on the Ion Exchange Properties of Caesium-Selective Ammonium Phosphomolybdate-Polyacrylonitrile (AMP-PAN) Composites under Spent Fuel Recycling Conditions

Abstract: The caesium radioisotopes 134Cs, 135Cs, and 137Cs are highly problematic medium-lived species produced during nuclear fission, due to their high radioactivity and environmental mobility. While many ion exchange materials can readily isolate Cs+ ions from neutral or basic aqueous solutions, only ammonium phosphomolybdate (AMP) functions effectively in acidic conditions, removing caesium even down to trace levels. Composites of AMP in a porous polymeric support such as polyacrylonitrile (PAN) can be used to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…γ irradiation is known to induce yellowing in PAN [24]. Pawde et al suggested that this effect could be exploited as an internal dosimeter, resulting from the formation of conjugated C=N bonds and cyclisation reactions within the polymer structure, [38] though in the case of AMP-PAN, the vibrancy of AMP's hue overpowers any colour change that could be observed in the PAN matrix, though for colourless or white composites, this factor could likely be exploited in applications such as those proposed here and previously by ourselves [21,22,30]. No change is observed to the morphology or XRD powder pattern of the AMP crystallites (Figures A2 and A3 respectively) upon irradiation [28,29].…”
Section: Chemical Changes Induced In Amp Upon Irradiationmentioning
confidence: 74%
See 4 more Smart Citations
“…γ irradiation is known to induce yellowing in PAN [24]. Pawde et al suggested that this effect could be exploited as an internal dosimeter, resulting from the formation of conjugated C=N bonds and cyclisation reactions within the polymer structure, [38] though in the case of AMP-PAN, the vibrancy of AMP's hue overpowers any colour change that could be observed in the PAN matrix, though for colourless or white composites, this factor could likely be exploited in applications such as those proposed here and previously by ourselves [21,22,30]. No change is observed to the morphology or XRD powder pattern of the AMP crystallites (Figures A2 and A3 respectively) upon irradiation [28,29].…”
Section: Chemical Changes Induced In Amp Upon Irradiationmentioning
confidence: 74%
“…A 70% (by weight) composite of AMP contained within a porous support substrate of PAN (henceforth referred to as AMP-PAN) was prepared as described in our previous publication [30], using a well-established method developed by Park et al [35], with modifications where noted [36]. An amount of 200 mL of DMSO was heated to 50 • C in a water bath with overhead stirring at 250 rpm, and mixed with 0.8 g of Tween 80.…”
Section: Materials and Amp-pan Composite Preparationmentioning
confidence: 99%
See 3 more Smart Citations